Defect distribution and compositional inhomogeneities in Al0.5Ga0.5N layers grown on stepped surfaces. (14th December 2015) - Mogilatenko, A; Knauer, A; Zeimer, U; Weyers, M
Abstract: This study reports on defect distribution and compositional homogeneity of Al x Ga1− x N layers with a nominal composition x of 0.5 grown on AlN by metal organic vapor phase epitaxy. The AlN layers with a low threading dislocation density (TDD) of a few 10 8 cm −2 were obtained by ELO and showed periodic surface macrosteps. Al x Ga1− x N growth on these AlN surfaces results in inhomogeneous Ga distribution due to enhanced Ga incorporation on the macrostep sidewalls. Variation of AlGaN deposition rate strongly influences the Ga distribution as well as the defect structure in the layers. Low growth rates (0.2 μ m h −1 ) result in an inhomogeneous TD distribution with formation of alternating stripes with lower and higher defect densities. Additionally, self-organized formation of additional Ga-rich areas at the top edge of the steps is observed. In contrast, at a higher growth rate of 1 μ m h −1 the formation of additional Ga-rich areas can be completely suppressed, but the defect density increases. This leads to an optimum growth rate to minimize the TDD.